Apocalypse Then, Now—and Future? - Bron Taylor (Ecocene: Cappadocia Journal of Environmental Humanities, 2020)
Since The Limits to Growth study in 1972 scores of studies have concluded that, without a dramatic reduction in human numbers and per-capita consumption and thus ecosystem destruction, and absent concomitant transformation of technological, economic, political, and value systems, widespread collapse of Earth’s socioecological systems will commence and accelerate during the 21st century. Although apocalyptic end-of-theworld-as-we-know-it expectations are historically longstanding and typically entangled with religious beliefs such expectations are now firmly grounded in the sciences. The apocalyptic imagination, whether traditionally religious or fueled by science typically avers that after the envisioned cataclysm a better existence is possible (if not certain), at least for the survivors (who are sometimes assumed to be the religiously devout). Science-based apocalypticism, however, increasingly projects an utterly bleak, biologically and socially impoverished future. Nevertheless, it remains possible that apocalyptic sciences and the imaginaries they have kindled, including as expressed by environmental humanities scholars and amplified by the voices (speaking metaphorically) of Earth’s suffering organisms and ecosystems, will precipitate a new era of cooperation and innovation and thus, not only avert widespread socioecological collapse, but kindle ecotopian visions futures.